Myten och dess arvtagare. Historiska och skönlitterära berättelser om folkhemmet - Żmuda-Trzebiatowska, Magdalena (De Gruyter Open‎, 2014)
The paper’s aim is to indicate the mutual relations between contemporary Swedish literature and the academic and political discourse on the welfare state’s crisis. The article’s first part discusses the genesis, evolution and meaning of the term ”Swedish folkhem” as it is understood today, i.e. as a political vision underlying the Swedish welfare state which with time has become a metaphor and a myth. In its other part the presence of historical narratives on the Swedish folkhem in five autobiographically inspired novels on childhood and growing up is investigated (Jonas Gardell’s "En komikers uppväxt" (1992), Lena Andersson’s "Var det bra så?" (1999), Mikael Niemi’s "Populärmusik i Vittula" (2000), Torbjörn Flygt’s "Underdog" (2001) and Susanna Alakoski’s "Svinalängorna" (2006). Analysing the chosen examples, the author of the paper focuses mainly on the issue of how the narratives known from political propaganda and debate are transformed, commented and used in a literary text to construct a collective identity.
Keywords: Gardell; Andersson; Niemi; Alakoski; Flygt; folkhemmet; välfärdstaten; historiska berättelser; svenska romaner; barndomsskildringar; kollektiv identitet; politisk myt; Swedish welfare state; Swedish folkhem; historical narratives; contemporary Swedish literature; novels on childhood; collective identity; political myth; szwedzkie państwo dobrobytu; narracje historyczne; współczesna literatura szwedzka; powieści o dzieciństwie; tożsamość zbiorowa; mit polityczny